Genome-wide identification, characterization and expression analysis of WRKY transcription factors under abiotic stresses in Carthamus tinctorius L - Zhengwei Tan; Dandan Lu; Yongliang Yu; Lei Li; Lanjie Xu; Wei Dong; Qing Yang; Chunming Li; Xiufu Wan; Huizhen Liang (BMC Plant Biology)
Abstract Background WRKY transcription factors constitute one of the largest families of plant transcriptional regulators, playing pivotal roles in plant responses to biotic and abiotic stresses, as well as in hormonal signaling and secondary metabolism regulation. However, a comprehensive analysis of the WRKY family in Carthamus tinctorius (safflower) is lacking. This study aims to identify and characterize WRKY genes in safflower to enhance understanding of their roles in stress responses and metabolic regulation. Safflower, valued for its ornamental, medicinal, and culinary uses, exhibits significant resilience to salt, alkali, and drought. By elucidating the functions and expression patterns of WRKY genes, we aim to enhance breeding strategies for improved stress tolerance and metabolic traits in crops. Results In this study, we identified 84 WRKY genes within the safflower genome, and classified them into three primary groups (Groups I, II, and III) based on molecular structure and phylogenetic relationships. Group II was further subdivided into five subgroups (II-a, II-b, II-c, II-d, and II-e). Gene structure, conserved domain, motif, cis-elements, and expression profiling were performed. Syntenic analysis revealed that there were 27 pairs of repetitive fragments. Expression profiles of CtWRKY genes were assessed across diverse tissues, colored cultivars, and abiotic stresses such as ABA, drought, and cold conditions. Several CtWRKY genes (e.g., CtWRKY44, CtWRKY63, CtWRKY65, CtWRKY70 and CtWRKY72) exhibited distinct expression patterns in response to cold stress and during different developmental stages. Additionally, CtWRKY13, CtWRKY69, CtWRKY29, CtWRKY56, and CtWRKY36 were upregulated across different flower colors. The expression patterns of CtWRKY48, CtWRKY58, and CtWRKY70 varied among safflower cultivars and flower colors. After exposure to drought stress, the expression levels of CtWRKY29 and CtWRKY58 were downregulated, while those of CtWRKY56 and CtWRKY62 were upregulated. Conclusion This study identified 84 WRKY genes in Carthamus tinctorius and classified them into three groups, with detailed analyses of their structure, conserved domains, motifs, and expression profiles under various stresses. Notably, several WRKY genes such as CtWRKY44, CtWRKY63, and CtWRKY72 displayed significant expression changes under cold stress, while CtWRKY56 and CtWRKY62 were responsive to drought stress. These findings highlight the critical roles of specific WRKY genes in abiotic stress tolerance and developmental regulation in safflower.